A Ni(OH)2–CoS2 hybrid nanowire array: a superior non-noble-metal catalyst toward the hydrogen evolution reaction in alkaline media. Issue 43 (31st October 2017) - Chen, Lanlan; Zhang, Jiayu; Ren, Xiang; Ge, Ruixiang; Teng, Wanqing; Sun, Xuping; Li, Xuemei
Abstract : A Ni(OH)2 –CoS2 nanowire array on a carbon cloth acts as a 3D catalyst electrode for a hydrogen evolution reaction, with only 99 mV overpotential to drive 20 mA cm −2 in 1.0 M KOH, 100 mV less than that of a CoS2 nanoarray. Abstract : The rising H2 economy urgently demands active, durable and cost-effective catalysts for the electrochemical hydrogen evolution reaction (HER). However, improving the HER performance of electrocatalysts in alkaline media is still challenging. Herein, we report the development of a nickel hydroxide–cobalt disulfide nanowire array on a carbon cloth (Ni(OH)2 –CoS2 /CC) as a hybrid catalyst to significantly enhance the HER activity in alkaline solutions. Benefitting from heterogeneous interfaces in this 3D hybrid electrocatalyst, Ni(OH)2 –CoS2 /CC shows superior HER activity with only 99 mV overpotential to drive a current density of 20 mA cm −2 in 1.0 M KOH, which is 100 mV less than that of CoS2 /CC. Moreover, Ni(OH)2 –CoS2 /CC exhibits long-term electrochemical durability with the maintenance of its catalytic activity for 30 h. Density functional theory calculations are performed to gain further insight into the effect of Ni(OH)2 –CoS2 interfaces, revealing that Ni(OH)2 plays a key role in water dissociation to hydrogen intermediates and CoS2 facilitates the adsorption of hydrogen intermediates and H2 generation. This work not only develops a promising electrocatalyst for the alkaline HER, but also paves a way to enhance the alkaline HER activity of CoS2 via the interface engineering strategy.